2016
DOI: 10.1088/0960-1317/26/9/095008
|View full text |Cite
|
Sign up to set email alerts
|

Design of a MEMS-based motion stage based on a lever mechanism for generating large displacements and forces

Abstract: Conventional miniaturized motion stages have a volume of 50-60 cm 3 and a range of motion around 100 μm. Micro-electro-mechanical systems (MEMS)-based motion stages have been good alternatives in some applications for small footprint, micron-level accuracy, and a lower cost. However, existing MEMS-based motion stages are able to provide a force of μN level, small displacements (less than tens of microns), and need additional features for practical applications like a probe or a stage. In this paper, a single d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the work of Bergna et al for nano-positioning systems, a MEMS chevron structure is implemented for a thermal actuator, demonstrating displacement of 5 µm [28]. This displacement is further amplified by flexure structures to strokes up to 80 µm [29].…”
Section: Indirect Leverage a Buckling And V-shaped Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Bergna et al for nano-positioning systems, a MEMS chevron structure is implemented for a thermal actuator, demonstrating displacement of 5 µm [28]. This displacement is further amplified by flexure structures to strokes up to 80 µm [29].…”
Section: Indirect Leverage a Buckling And V-shaped Beamsmentioning
confidence: 99%
“…A characteristic example of optimized linear and rotational MEMS flexures is the Si flexures of Kim et al shown in Fig. 11 [29].…”
Section: Flextensional Mechanismsmentioning
confidence: 99%
“…Micro-Electro-Mechanical Systems (MEMS) service platforms are attractive in various applications, such as micro motors, micro robots and micro optical lens scanners [1][2][3][4][5][6][7][8][9][10]. Most MEMS service platforms are composed of MEMS actuators, flexure pivots, springs and shuttles that are designed to produce appropriate motions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a motion stage based on lever mechanism was reported to achieve almost 100 µm by utilizing electro-thermal actuation [7]. An electrothermal actuator with displacement larger than 200 µm microns was achieved in [8].…”
Section: Introductionmentioning
confidence: 99%